Organoprotecive effects of angiotensin II receptor blockers in patients with type 2 diabetes mellitus - Ivona Yanovna Yarek-Martynova; Minara Shamkhalovna Shamkhalova (Сахарный диабет)
High prevalence of arterial hypertension and related cardiovascular complications dictates the necessity of preparations possessed of markedorganoprotective activity and good tolerability. The currently available data suggest advantages of iACE and ARB as preparations for the treatmentof cardiovascular diseases such as ability of iACE to improve clinical picture and outcome of therapy of cardiac insufficiency, left ventricle dysfunction,and myocardial infarction. Large-scale prospective studies demonstrated effectiveness of these agents in the treatment of CHD, stroke, diabetes, renalpathology and revealed their additional advantages attributable to inhibition of angiotensin II secretion other than those related to reduction of AP.These studies gave evidence of a more pronounced decrease in the frequency of cardiovascular events under effect of ARB in high-risk patients. However,protective action of ARB on the cardiovascular system compared with that of iACE and combination of ARB+iACE awaits an in-depth study.